The Relationship Between Healthy Food Choices and Calcium Intake in Dysmenorrhea Adolescents - Shinta; Didik Gunawan Tamtomo; Ratih Febrinasari Puspitasari (Future Science, 2024)
Several factors that can affect primary dysmenorrhoea are poor dietary habits and low intake of macro and micronutrients. One of the micronutrients that affect dysmenorrhoea is calcium intake. Calcium plays a role in regulating the work of hormones in growth. Calcium deficiency can encourage overproduction of prostaglandins which can lead to uncontrolled uterine contractions that can trigger pain. Based on data from the USDA Nationwide Food Consumption Survey in 48 countries, the average calcium intake at the age of 15-18 years is less than 70% of the RDA. A preliminary study conducted by the author at a public high school in Padang found that 80.2% had primary dysmenorrhoea. Individual eating habits can have an impact on behavior related to healthy food choices and can affect nutritional intake including calcium intake. This study aims to determine the relationship between healthy food selection and calcium intake in adolescent girls who experience primary dysmenorrhoea. 100 respondents were determined using the Slovin formula with the criteria of female students aged 15-18 years who experienced primary dysmenorrhoea. Data collection on healthy food choices was measured using a questionnaire of healthy food choices which consists of 30 statements with a score for selecting important healthy foods > 120. Calcium intake data uses the SQ-FFQ form with the adequate calcium intake category ? 1200 mg/day. Data analysis using Spearman rank correlation test. The results of statistical tests show that there is a relationship between healthy food choices and calcium intake (r = 0.23, p = 0.021). The results of this research can be used as a basis for providing therapeutic options for dysmenorrhoea. The implications for young women are knowing comprehensively the importance of choosing healthy foods and calcium intake to reduce the pain of primary dysmenorrhoea.